Reform and renewables in China: The architecture of Yunnan's hydropower dominated electricity market. (October 2018) - Cheng, Chuntian; Chen, Fu; Li, Gang; Ristić, Bora; Mirchi, Ali; Qiyu, Tu; Madani, Kaveh
Abstract: Reforms currently under way in China's electricity markets bear important implications for its decarbonization objectives. The southwestern province of Yunnan is among the provinces piloting the current iteration of power market reforms. As such, lessons from Yunnan will inform future market reform and renewable energy policies in China and potentially elsewhere. The dominance of hydropower in Yunnan's energy portfolio and the particular transmission constraints it faces, offer an interesting case study of the challenges of decarbonization. We report on market architecture reforms and aggregate market data collected from the Yunnan Power Exchange. We review four elements in the reformed market architecture. Market pricing rules, transitional quantity controls, the generation rights market, and inter-provincial trade. The specifics of market reform reflect a compromise between decarbonization, inter-provincial competition, grid security and development objectives and contribute to understanding of how the dual transitions of hydropower decarbonization and market liberalization interact. We conclude on six insights regarding the role of the grid operator, security checks on trade, integration of cascade hydropower, the inclusion of renewables in the generation rights market, price controls, and market participant price uncertainty. Highlights: Yunnan's electricity market suffers from hydropower oversupply and low demand. Market reform has supported decarbonization and spillage reduction. Generation rights and interprovincial trade were particularly helpful in this regard. Electricity trade remains controlled due to compromises between competing policy constraints. Opportunities for further reform and potentially feasible recommendations are discussed.